Clinical feasibility of cognitive testing in dogs (Canis lupus familiaris) - Heckler, Marta C. T. [UNESP]; Tranquilim, Marcos V. [UNESP]; Svicero, Denis J. [UNESP]; Barbosa, Luciano [UNESP]; Amorim, Rogerio M. [UNESP] (Elsevier B.V., 2014)
Several cognitive tests have been developed to evaluate specific aspects of human and animal learning and memory. These tests have been used for early detection of cognitive deficits and to monitor the treatment of dogs with cognitive impairment. Thus, this article evaluated the feasibility of cognitive tests for use in canine neurology clinical routines and the suitability of the different tests to accomplish this aim. Fifteen healthy adult dogs were used for the cognitive tests of reward approach learning, object approach learning, object discrimination learning, reversal learning, delayed non-matched to position, and delayed non-matched to sample to assess different aspects of memory. No difference was observed between tests of delayed non-matched to position (3.13 +/- 2.23 days) and delayed non-matched to sample (3.20 +/- 2.40 days) (P = 0.944). However, dogs had greater difficulty in reversal learning (8.47 +/- 2.61 days) than in object discrimination learning (4.60 +/- 1.64 days) (P <= 0.001). Based on the tests performed, the delayed non-matched to position test may be performed in clinical routine if the owner and the veterinarian have time available, because this test is sensitive to evaluate dogs with cognitive impairments, but requires approximately 10 days of training. Thus, elderly dogs are excellent experimental models to study pathological aging based on their similarities with some human brain diseases, such as Alzheimer disease. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: cognition; canine; cognitive dysfunction syndrome; memory; discrimination learning